PKM PELATIHAN KARYA TULIS ILMIAH AL-QUR’AN (KTIQ) BAGI SANTRI MADRASAH ALIYAH (MA) PONDOK PESANTREN MIZANUL ULUM SANROBONE KABUPATEN TAKALAR, SULAWESI SELATAN - Muhajir, Muhajir; Syamsu, Awaluddin; Akidah, Ihramsari; Mansyur, Umar (LPPM Universitas Al Muslim, 2024)
The Scientific Writing Competition of the Quran (KTIQ) at the Musabaqah Tilawatil Quran (MTQ) level is usually participated by students of Islamic boarding schools. Mizanul Ulum Sanrobone Islamic Boarding School of Takalar Regency routinely assigns its students as delegates to participate in the KTIQ competition, both at the district and provincial levels, and the results of the rankings obtained have not been optimal. Therefore, an approach is needed in the form of KTIQ writing training for students of Mizanul Ulum Islamic Boarding School as a real solution to the problems of the students in facing each MTQ event. The results of the implementation of this community service activity are expected to be an alternative solution for students of Mizanul Ulum Islamic Boarding School, Sanrobone in facing each Musabaqah Tilawatil Quran (MTQ) event. This training has contributed to the students as training participants through three KTIQ writing standards, namely: 1) the field of material weight, 2) the field of language rules and style, and 3) the field of logic and message organization. In addition, in this training, participants have also been provided with knowledge of assessing each content in the standard.